Fıxed Herbst Applıance-Occıpıtal Headgear Combınatıon In Hıgh Angle Skeletal Class Iı Cases: Report Of Two Cases - Eray Erdoğan (Turkish Journal of Orthodontics, 1995)

(untitled)
Fixe Herbst appliance-occipital headgear combination in mixed dentition results positively, in severe high angle Class II cases. This orthopedic approach was applied in two cases who had maxillary excess and mandibular insufficiency, and increased vertical dimensions; positive skeletal and dental effects were noted. In this article, the advantages and disadvantages of this approach will be discussed with the presentation of these two cases resulted with a good skeletal correction.